Pengembangan Video Pembelajaran Untuk Pengenalan Kosa Kata Bahasa Arab Anak Usia Dini Berbasis Aplikasi Inshot - Maharani, Dini; Warmansyah, Jhoni (JOSTECH: Journal of Science and Technology, 2022)
This study aims to develop an inshot application-based learning video for early childhood Arabic vocabulary introduction (AUD). The type of research used is research and development (R&D) research using a 4D development model, but in this study it is only limited to 3 stages, namely the definition stage, the design stage, and the develop stage. This research was conducted at TKIT Qurrata A'yun Batusangkar. Based on the validity and practicality test of learning video media products using the inshot application for the introduction of Arabic vocabulary in children, it appears that this media is very valid and very practical. . This is indicated by the results of the validity with a percentage of 83.75% with very valid criteria and the results of the test results with a percentage of 97.5% with very practical criteria.